The Combined Utilization of Epithelial Thickness and Tomographic Parameters in Keratoconus Detection - Abdelrahman Salman; Mayank Nanavaty; Rana Omran; Marwan Ghabra; Obeda Kailani; Rafea Shaaban; Taym Darwish; Buraa Kubaisi; Zein Baradi; Mohamed Khallouf; Omar Badla (Journal of Ophthalmology)
Conclusion: Both combined AS-OCT indices and combined SPT indices provided excellent diagnostic power to differentiate SKC from N eyes. The combined SPT model showed a superior value compared to the AS-OCT model. Furthermore, combined AS-OCT and SPT data did not perform better than the combined SPT data alone.